Mucocele of the Appendix: Two Case Reports - Azoz, Mohammed E H; Makkawi, Abdelmoniem M M; Fadolalnabi, Ahmed Abdelrahman; Alhasan Ali, Moataz Mohamed (Gezira Journal of Health Sciences, 2017)
Introduction: Appendiceal mucocele is a rare condition which was described as an obstructive dilatation of the appendix caused by intraluminal accumulation of mucoid material. Case Reports: We present a case of 26 years old male who came for elective appendectomy which intraoperatively found to have  mucocele of appendix which was treated successfully by appendicectomy. The second case was a 55 years female who presented with a right iliac fossa mass with mesenteric lymph nodes enlargement ,underwent right hemicolectomy and the histopathological report showed mucinous cystadenoma of the appendix. Conclusion: In conclusion, appendiceal mucocele is a rare disease and has a clinical presentation that resembles acute appendicitis or RIF Tumour.